To Conscience First, and to the Pope (Long) Afterwards? British Catholics and Their Attitudes Towards Morality and Structural Issues Concerning the Catholic Church - Clements, Ben (Review of religious research, 2021)
BackgroundThe attitudes of Catholics in Britain have undergone significant liberalisation on social moral issues across recent decades, whilst the reputation of the Catholic Church has suffered due to public opposition to its traditional teachings on such issues. But there has been comparatively little recent investigation into British Catholics’ views on these debates using surveys aimed at this religious community.PurposeThis article examines the sources of attitudinal heterogeneity amongst Catholics in Britain on core debates affecting the Catholic Church. The aims are to examine, firstly, which groups within the British Catholic Community are more likely to conform to or to dissent from the Church’s teachings and, secondly, whether the socio-demographic and religious correlates of attitudes vary across different types of issue.MethodsThis article uses a new, nationally representative survey of Catholic adults in Britain (n = 1823). The survey is used to examine the sources of variation in Catholics’ attitudes towards a range of issues relating to the Roman Catholic Church. These issues relate to the priesthood, personal morality, and sinful behaviours. OLS models are used to assesses the relative impact of socio-demographic, religious socialisation, and religious commitment variables.ResultsThe findings show that women are consistently more liberal in their views than men. Greater religious commitment is always associated with support for the traditional teachings of the Church.Conclusions and ImplicationsExploring the sources of attitudinal heterogeneity among Catholics, we provide new insights into the internal dynamics of ‘Britain’s largest minority’. We conclude by discussing the potential effects of increasing ‘nonversion’ for interpreting religious statistics—a topic of relevance beyond the denominational and geographical confines of this study’s explicit focus.